1967
DOI: 10.1677/joe.0.0370361
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Progesterone on Body Weight and Composition in the Rat

Abstract: SUMMARY The effects of progesterone administration on the weight and composition of the body have been studied in rats. Female rats injected with 5 mg. progesterone/day initially gained weight at an average rate of 2 g./day, compared with 0·4 g./day for controls. When treatment was continued for a month or more their weight stabilized at 40–50 g. above the control level. The bodies of the progesterone-treated rats contained increased amounts of water, fat and solids other than fat. These effects were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
2
2

Year Published

1972
1972
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(89 citation statements)
references
References 0 publications
5
80
2
2
Order By: Relevance
“…The effects of nutrition may be further confounded by the possible effect of progesterone on body weight changes (Gilbert & Gillman, 1956;Dewar, 1957;Hervey & Hervey, 1967 …”
Section: Plane Of Nutrition and Progesterone Concentrationmentioning
confidence: 99%
“…The effects of nutrition may be further confounded by the possible effect of progesterone on body weight changes (Gilbert & Gillman, 1956;Dewar, 1957;Hervey & Hervey, 1967 …”
Section: Plane Of Nutrition and Progesterone Concentrationmentioning
confidence: 99%
“…Whether progesterone also acts directly on rat mammary tissue in this way is unknown. Available evidence suggests that progesterone may stimulate breast tissue indirectly via the hypothalamus and pituitary gland, the effect being due to increased secretion of prolactin (LTH) and possibly also growth hormone (STH) (Huggins, Mainzer and Briziarelli, 1958;Rothchild, 1960;Kim, 1965;Clementi and De Virgiliis, 1967;Hervey and Hervey, 1967;Sar and Meites, 1968;Welsch et al, 1968). Both LTH and STH have been shown to stimulate markedly mammary growth in rats, even in the absence of the pituitary gland and ovaries (Furth and Clifton, 1957;Talwalker and Meites, 1961;Dao and Gawlak, 1963;Talwalker, Meites and Mizuno, 1964;Sinha and Tucker, 1968;Takizawa, Furth and Furth, 1970).…”
Section: Discussionmentioning
confidence: 99%
“…As in obesity induced by a high-fat diet, no overeating was observed, but excessive fat development could be related to a decrease of spontaneous activity. Progesterone promotes body weight gain (Bourdel and Jacquot, 1965) by increasing the adipose mass (Hervey and Hervey, 1967 ;Krotkiewski and Bj6rntorp, 1976). The administration of progesterone seems to reproduce the physiological situation of pregnancy, weight gain being supplied by 30 to 40 p. 100 of fat (Hervey and Hervey, 1967).…”
Section: Methodsmentioning
confidence: 99%
“…Progesterone promotes body weight gain (Bourdel and Jacquot, 1965) by increasing the adipose mass (Hervey and Hervey, 1967 ;Krotkiewski and Bj6rntorp, 1976). The administration of progesterone seems to reproduce the physiological situation of pregnancy, weight gain being supplied by 30 to 40 p. 100 of fat (Hervey and Hervey, 1967). Birke and Archer (1975) and Guttman et al (1975) found variations in locomotor activity and behavioral response in an open field during the murine estrous cycle.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation